Botanical composition and carrying capacity of the timor deer (Cervus timorensis) breeding facility owned by PT Pulau Lemon in Maruni Village Manokwari Selatan - Penehas Magai; Evi W. Saragih; Hotlan Manik (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2026)
This study aimed to evaluate the botanical composition and carrying capacity of grazing pasture as the main feed resource for Timor deer (Cervus timorensis) at the captive breeding facility of PT Pulau Lemon, Manokwari, West Papua. A descriptive case study approach was applied using quadrat sampling (1 m × 1 m) at ten sampling points representing vegetation heterogeneity and site topography. All forage species within each quadrat were harvested, identified to species level, and weighed to determine fresh biomass production and botanical composition. Carrying capacity was estimated based on available forage biomass, proper use factor, and livestock unit conversion. The results showed that ten plant species were recorded, consisting of four grasses, two legumes, and four other forages. Grasses dominated the pasture cover, while legumes occurred at relatively low frequency. Based on fresh weight proportion, non‑grass forages accounted for the largest fraction, including both edible and non‑edible species. The available consumable forage production averaged 0.146 kg m⁻², resulting in a carrying capacity of only 1.67 livestock units ha⁻¹ year⁻¹, equivalent to approximately four adult deer (35 kg body weight) for the total grazing area of 1.75 ha. Continuous grazing and high stocking density were identified as major factors contributing to low forage productivity and pasture degradation. In conclusion, the current grazing area is unable to support the existing deer population sustainably, indicating an urgent need for pasture improvement, rotational grazing, and population management.